A cross-sectional study of factors influencing purchasing cars in European Union – does the electric and hybrid cars change the contemporary business approach? - Popescu, Gheorghe H.; Andrei, Jean Vasile; Sima, Violeta; Nica, Elvira; Chivu, Luminita; Gheorghe, Ileana Georgiana (Journal of Business Economics and Management, 2024)
This study aims to examine the expansion of the electric vehicle fleet in the context of transport electrification in the European Union. We assessed the car market, following demand and sales trends for electric and hybrid cars. It was explored the possibility of a causal relationship among the percentage of BEV + PHEV in the total fleet and purchasing power, loading infrastructure, government support, the level of education and the degree of digitalization. To achieve the main objectives of the research to assess the existence and magnitude of the causal effects of the considered variables on the percentage of BEV + PHEV in the total fleet, we conducted a cross-sectional analysis in 2020 among the European Union (EU) countries. Five research hypotheses were formulated and tested. The results confirmed that the economic and social development of a region, the charging infrastructure, the government support measures, and the degree of digitalization positively influence the desire of the EU population to buy electric cars.